AQUEOUS TWO-PHASE POLYMER MIXTURE SYSTEM AS PROTEIN XTRACTION TECHNIQUE. MODELLING OF PROTEIN PARTITIONING BEHAVIOR - Ahmad, Murni M (2007)
Aqueous Two-Phase Extraction System has the otential as an efficient yet inexpensive, large-scale extraction for high-value proteins as it provides a mild environment for proteins, allows integration with upstream process, offers high yield and eliminates a large portion of the contaminating lysate. However, the realization of these systems as a new protein separation technology at industrial scales is rather limited. Among the reasons are the fact that the selection of phase-forming agents can be exhaustive as there are many tuneable parameters, efforts are mostly empirical and intuitive with many possibilities and there are limited design approaches capable of accurate prediction of system and product behaviour that offer large scope of application with operation assessment and performance sensitivity. Hence, a computational approach is proposed to calculate the equilibrium behaviour of a common type, i.e. aqueous polymer-mixture systems, and the protein partitioning behaviour in such systems to allow further study on its extraction potential. A Gibbs energy of mixing minimization approach is presented to calculate the liquid-liquid equilibrium behaviour and protein partitioning behaviour in the polymer-mixture ATPES that is based on Flory-Huggins polymer theory. The minimization problem is solved using the modified Shor's R-algorithm for non-smooth optimization. The applicability of the approach is demonstrated by simulating the thermodynamic behaviour of water-PEG6000-DxT500 system and the selective partitioning behaviour of phosphofructokinase and ovalbumin in this system. Some issues involved in solving for the LLE compositions are discussed and methods and steps taken to achieve robust, accurate and reliable simulations are presented. The comparison between our results is made against the calculations of Johansson et al. (1998) and the experimental data of Albertsson et al (1987).